2019
DOI: 10.1101/2019.12.13.875146
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

BZIP Transcription Factors Modulate DNA Supercoiling Transitions

Abstract: Torsional stress on DNA, introduced by molecular motors, constitutes an important regulatory mechanism of transcriptional control. Torsional stress can modulate specific binding of transcription factors to DNA and introduce local conformational changes that facilitate the opening of promoters and nucleosome remodeling. Using all-atom microsecond scale molecular dynamics simulations together with a torsional restraint that controls the total helical twist of a DNA fragment, we addressed the impact of torsional … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Several bZIP TFs have been shown to function as pioneer TFs, able to displace nucleosomes in chromatin inaccessible to other TFs, thus enabling the assembly of other TFs ( 62 , 63 ). It has recently been hypothesized that some bZIP proteins inhibit chromatin compaction, initiating the formation of enhanceosomes (higher-order multicomponent TF–enhancer complexes) ( 64 ). Optimal positioning of pioneer TFs, in particular, has been suggested to be necessary for gene expression ( 65 ), which could explain the significant impact of relocation (Figure 1C ).…”
Section: Discussionmentioning
confidence: 99%
“…Several bZIP TFs have been shown to function as pioneer TFs, able to displace nucleosomes in chromatin inaccessible to other TFs, thus enabling the assembly of other TFs ( 62 , 63 ). It has recently been hypothesized that some bZIP proteins inhibit chromatin compaction, initiating the formation of enhanceosomes (higher-order multicomponent TF–enhancer complexes) ( 64 ). Optimal positioning of pioneer TFs, in particular, has been suggested to be necessary for gene expression ( 65 ), which could explain the significant impact of relocation (Figure 1C ).…”
Section: Discussionmentioning
confidence: 99%
“…shift when a transcription factor is bound to DNA, directly translates into DNA local twist flexibility, and consequently the energetic cost of DNA supercoiling transitions. 11 The described molecular mechanism, we believe, allows the transcription factor to regulate the opening of gene promoters and subsequently their firing potentials, and by extension, the gene expression levels.…”
Section: Resultsmentioning
confidence: 93%
“…50 Together with writhe, twist modulates DNA supercoiling transitions along the chromatin fibre. Recently, we have shown that MafB (a member of human BZIP family) 11 asymmetrically changes the sequence-specific response of DNA to torsional stress, making DNA effectively more rigid. The molecular mechanism of the observed phenomenon is based upon MafB forming a number of specific contacts with the torsionally flexible YR dinucleotide steps thus restraining their shift.…”
Section: Helical Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Several bZIP TFs have been shown to function as pioneer TFs, able to displace nucleosomes in chromatin inaccessible to other TFs, thus enabling the assembly of other TFs (59,60). It has recently been hypothesised that some bZIP proteins inhibit chromatin compaction, initiating the formation of enhanceosomes (higher-order multicomponent transcription factorenhancer complexes) (61). Optimal positioning of pioneer TFs, in particular, has been suggested to be necessary for gene expression (62), which could explain the significant impact of relocation ( Figure 1C).…”
Section: Discussionmentioning
confidence: 99%